# Determining the heat of a reaction

Determine the heat of reaction for the oxidation of iron,

4 Fe 9 (s) + 3 O--->  2 Fe2O3 (s)

given the enthalpies of the reactions below.

2 Fe (s) + 6 H20 (l) ---> 2 Fe(OH)3 (s) + 3 H2 (g)   change in enthalpy = 321.8 kJ

2 H2 (g) + O2 (g) ---->  2 H2O (l)    change in enthalpy =  -571.7 kJ

Fe2O3 (s) + 3 H2O (l) ----> 2 Fe(OH)(s)   change in enthalpy = 288.6 kJ

The answer is -1648.7 kJ, but i don't understand what to do to solve this problem.  I need to know what to do starting from the beginning.  Thank you for any help.

### Ignore theĀ 9 in the very

17Soccer Sat, 11/05/2016 - 22:20

Ignore the 9 in the very first equation after the 4 Fe. it was a typo

### (Twice the equation 1) +

Divikjainchem Tue, 11/22/2016 - 12:32
(Twice the equation 1) + (thrice the equation 2) - (twice the equation 3) = required equation . A simple application of Hess's Law

### You will use Hess's law to

chemtopper Tue, 11/22/2016 - 19:25

You will use Hess's law to solve this question.Review this topic.

2 Fe (s) + 6 H20 (l) ---> 2 Fe(OH)3 (s) + 3 H2 (g)   change in enthalpy = 321.8 kJ---1

2 H2 (g) + O2 (g) ---->  2 H2O (l)    change in enthalpy =  -571.7 kJ-----2

Fe2O3 (s) + 3 H2O (l) ----> 2 Fe(OH)3  (s)   change in enthalpy = 288.6 kJ------3

To get the desired equation

4 Fe  (s) + 3 O2  --->  2 Fe2O(s)

Multiply eq -1 with 2 ,eq -2 with 3 and reverse eq 3 and multiply it with 2 ...

you will get new sets of equations

4 Fe (s) + 12 H20 (l) ---> 4 Fe(OH)3 (s) + 6 H2 (g)   change in enthalpy = 2*321.8 kJ---1

6 H2 (g) + 3O2 (g) ---->  6 H2O (l)    change in enthalpy =3*  -571.7 kJ-----2

4 Fe(OH)3  (s) ---->2Fe2O3 (s) + 6 H2O (l)  change in enthalpy =2* - 288.6 kJ------3

add all three equations and cancel common substances on different sides of the  equations and check that you will get your desired reaction.